Viabilidade da implantação de sistemas agroflorestais na Comunidade São Sebastião do Saracá, RDS Rio Negro, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Possible paths for the development of economically sustainable activities in RDS are agrofo-restry systems (SAFs). However, for these systems to be considered sustainable given the conditions of the territory, studies are needed to confirm the feasibility of their implementation. Thus, this study aimed to evaluate the feasibility of implementing agroforestry systems in the community of São Sebastião do Saracá, municipality of Iranduba, Sustainable Development Reserve of Rio Negro, Amazonas, in order to reconcile production and sustainability of existing natural resources. The research had the participation of 21 families. The methodology used for data collection considered the use of semi-structured questionnaires, interviews, focus groups, floristic survey, systematic mapping of forest species indicated by the communities, soil analysis and financial analysis considering the indicators VPL, TIR, TMA, Payback time and C/B ratio. The results obtained in this study indicated that, from a socioeconomic point of view, the implementation of SAFs in the community would bring benefits aimed at diversifying the sources of income for families, in addition to conserving natural resources. As for the selection of species for the composition of the SAFs, a preference for native forest species was identified, mainly in view of the utilitarian values of these species for the construction of furniture and handicrafts. However, for the implementation of SAFs to be success-ful, the need for investments in liming and fertilization was identified, as the soils of the community have high acidity, low levels of N, P, K. In terms of the results of the feasibility analysis financial, it was identified that the implementation of SAFs is viable, because despite the high cost of implementing the system, justified by the need for fertilization, the financial viability was confirmed thanks to the different recipes, consisting of fruit species, oil species, species that produce seeds, almond-producing species and wood species. Therefore, it is concludes that there is feasibility in the implementation of agroforestry systems in the São Sebas-tião do Saracá community.
Keywords: CIENCIAS AGRARIAS; SAFs; Espécies florestais nativas; Plantio, Conservação.